Measuring the Adoption of CSR in Human Rights Perspective (Journal of Governance and Development (JGD), 2012)
Corporations have become one of the vital actors during its development. Even if the corporations' accomplishments are strongly induced by the interests of the owners of capital, there remains a strong relationship between the advancement of corporate interests with the quality of life of society. Business and human rights have a strong and functional inter-correlation. The emergence of the concept of corporate social responsibility demonstrates a strong desire to designate and ensure the efforts of protection and fulfillment of human rights as a duty and responsibility of corporations. Unfortunately, the adoption of the concept of CSR in Indonesia still finds compelling stagnation, particularly in aggregating and articulating the real interests of society and obligations of the corporation in promoting and fulfilling human rights.